Monetary incentives in primary health care and effects on use and coverage of preventive health care interventions in rural Honduras: cluster randomised trial - Morris, Saul S; Flores, Rafael; Olinto, Pedro; Medina, Juan Manuel (The Lancet (British edition), 2004)
Scaling-up of effective preventive interventions in child and maternal health is constrained in many developing countries by lack of demand. In Latin America, some governments have been trying to increase demand for health interventions by making direct payments to poor households contingent on them keeping up-to-date with preventive health services. We undertook a public health programme effectiveness trial in Honduras to assess this approach, contrasting it with a direct transfer of resources to local health teams. 70 municipalities were selected because they had the country's highest prevalence of malnutrition. They were allocated at random to four groups: money to households; resources to local health teams combined with a community-based nutrition intervention; both packages; and neither. Evaluation surveys of about 5600 households were undertaken at baseline and roughly 2 years later. Pregnant women and mothers of children younger than 3 years old were asked about use of health services (primary outcome) and coverage of interventions such as immunisation and growth monitoring (secondary outcome). Reports were supplemented with data from children's health cards and government service utilisation data. Analysis was by mixed effects regression, accounting for the municipality-level randomisation. The household-level intervention had a large impact (15–20 percentage points; p<0·01) on the reported coverage of antenatal care and well-child check-ups. Childhood immunisation series could thus be started more opportunely, and the coverage of growth monitoring was markedly increased (15–21 percentage points; p<0·01. Measles and tetanus toxoid immunisation were not affected. The transfer of resources to local health teams could not be implemented properly because of legal complications. Conditional payments to households increase the use and coverage of preventive health care interventions.